2006
DOI: 10.1111/j.1439-037x.2006.00217.x
|View full text |Cite
|
Sign up to set email alerts
|

Wounding of Root or Basal Stalk Prior to Harvest Affects Pre‐harvest Antioxidant Accumulation and Tobacco‐specific Nitrosamine Formation during Air Curing of Burley Tobacco (Nicotiana tabacum L.)

Abstract: Wounding stresses were tested for their ability to induce an accumulation of antioxidants in harvested tobacco (Nicotiana tabacum L.) and for the reduction of tobacco-specific nitrosamines (TSNA) during subsequent air curing. Data indicated that root pruning of burley tobacco 1 week before harvest resulted in an increased accumulation of a-tocopherol, chlorogenic acid and rutin, compared with untreated plants. Wounding also increased total antioxidant capacity in both green and cured tobacco. Field experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…When a plant suffers the attack of above-ground insects or herbivores it usually faces damage to the aerial tissues (leaves and stems), which results in a reduced photosynthetic area that needs to be restored, but the root system is left mostly intact [ 23 , 26 ]. On the contrary, de-rooted plants suffer no immediate damage to their photosynthetic tissues but are left with a severely reduced root area (non-existent in the case of TDR plants), which will greatly compromise their water and nutrient uptake capabilities [ 27 ]. This is very similar to the effect observed in plants that have been attacked by root herbivory [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…When a plant suffers the attack of above-ground insects or herbivores it usually faces damage to the aerial tissues (leaves and stems), which results in a reduced photosynthetic area that needs to be restored, but the root system is left mostly intact [ 23 , 26 ]. On the contrary, de-rooted plants suffer no immediate damage to their photosynthetic tissues but are left with a severely reduced root area (non-existent in the case of TDR plants), which will greatly compromise their water and nutrient uptake capabilities [ 27 ]. This is very similar to the effect observed in plants that have been attacked by root herbivory [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…This difference was significant at the P < 0.0001 level (Figure 4), and demonstrated the effective-ness of the RNAi mechanism in dramatically decreasing nicotine demethylase activity at either low or high levels of DH98-325-5 materials evaluated in the current investigation, NNN was at much higher levels than NNK, despite the fact that nicotine was by far the most prevalent alkaloid (Table 1). Strong relationships have been reported previously between nornicotine and NNN in burley tobacco, whereas relationships between nicotine and NNK are weaker (Bush et al ., 2001;Li et al ., 2006). The formation of NNK from nicotine may also be more complicated at the biochemical level when compared with the pathway of formation for NNN, NAB and NAT.…”
Section: Multi-environment Evaluation For Nornicotine Formation and Tmentioning
confidence: 99%
“…An important breakthrough toward understanding the molecular genetic basis of nornicotine biosynthesis came with the characterization of a tobacco cytochrome P450 gene, designated CYP82E4, mediated senescence induced nornicotine production (Siminszky et al, 2005;Chakrabarti et al, 2007;Gavilano et al, 2007;Xu et al, 2007), especially in Nicotiana species Burley (Li, 2006). Genetic transformation with CYP82E4 into yeast or transgenic tobacco revealed that the gene actively catalyzed the conversion of nicotine to nornicotine (Siminszky et al, 2005;Xu et al, 2007;Siminszky et al, 2005).…”
Section: A N U S C R I P Tmentioning
confidence: 99%